2023
DOI: 10.1136/bmjgh-2022-010994
|View full text |Cite
|
Sign up to set email alerts
|

Where are the missing people affected by tuberculosis? A programme review of patient-pathway and cascade of care to optimise tuberculosis case-finding, treatment and prevention in Cambodia

Abstract: BackgroundCambodia has achieved great success in tuberculosis (TB) control in the past decade. Nevertheless, people with TB are missed by the health systems at different stages of the care pathway. This programme review corroborated the care-seeking behaviours of people with TB and TB services availability and estimated the number of people completing each step of the TB disease and TB preventive treatment (TPT) care cascade.MethodsPatient pathways and the care cascades for TB disease and TPT were constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Some PPA studies have revealed a lack of basic information on TB diagnostic service availability in the private sector, as government regulatory agencies do not cover private facilities comprehensively. 3 , 7 , 12 Yet in Asia and Africa, engaging the private sector has been shown consistently to increase TB case detection and improve treatment outcomes, and various models for partnership exist. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some PPA studies have revealed a lack of basic information on TB diagnostic service availability in the private sector, as government regulatory agencies do not cover private facilities comprehensively. 3 , 7 , 12 Yet in Asia and Africa, engaging the private sector has been shown consistently to increase TB case detection and improve treatment outcomes, and various models for partnership exist. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Some PPA studies have revealed a lack of basic information on TB diagnostic service availability in the private sector, as government regulatory agencies do not cover private facilities comprehensively. 3,7,12 Yet in Asia and Africa, engaging the private sector has been shown consistently to increase TB case detection and improve treatment outcomes, and various models for partnership exist. 13 Despite private health-care providers playing an increasingly significant role in health-care delivery in Latin American nations, the literature on the involvement of private healthcare providers in TB detection and management for this region is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Some PPA studies have revealed a lack of basic information on TB diagnostic service availability in the private sector, as government regulatory agencies do not comprehensively cover private facilities. 3,7,11 Yet in Asia and Africa, engaging the private sector has consistently been shown to increase TB case detection and improve treatment outcomes, and various models for partnership exist. 12 Despite private healthcare providers playing an increasingly significant role in healthcare delivery in Latin American nations, the literature on the involvement of private healthcare providers in TB detection and management for this region is limited.…”
Section: Introductionmentioning
confidence: 99%